Answer:
Step-by-step explanation:
Lets start with 13
-2(13 + 3) = -4(13) + 20
-32 = -52 + 20
-32 = -32
x = 1 basically
now 19
-2(19 + 3) = -4(19) +20
-44 = -76 + 20
-44 = -56
so divide those
-2(31 + 3) = -4(31) + 20
-68 = -124 + 20
-68 = -104
divide them
-2(37 + 3) = -4(37) + 20
-80 = -148 + 20
-80 = -128
1/10 is equal to 100/1000, as that way, both the numerator and the denominator are multiplied by 100.
This works because the number multiplying the top and bottom are equal, therefore resulting in no net change.
Answer:
a = b/4
Step-by-step explanation:
Note that the LCD in this equation is 6. Rewriting 2a-b/6 = b/3 using this LCD, we get:
2a-b/6 = 2b/6
Multiplying all three terms by 6 eliminates the fractions:
12a - b = 2b
Combining like terms:
12a = 3b
3b
Solving this for a, we get a = ------------ = b/4
12
a = b/4
Area = A = πr²
Circumference = C = 2πr